Clinical outcomes of pacemaker implantations before and after cancer diagnosis. (14th October 2021) - Riesenhuber, M; Spannbauer, A; Gwechenberger, M; Pezawas, T; Schukro, C; Stix, G; Goliasch, G; Anvari, A; Wrba, T; Khazen, C; Andreas, M; Laufer, G; et al.
Abstract: Background: Cardiotoxicity caused by anticancer treatment affects cardiac conduction. Clinical outcomes of pacemaker patients with newly diagnosed cancer are insufficiently understood. Purpose: The aim was to investigate the effect of anticancer therapy on pacemaker properties. Methods: All patients with pacemaker and confirmed cancer diagnosis treated with chemotherapy at our tertiary university hospital were included in this study. The pacemaker database (containing pacemaker related information) was matched with hospital-wide electronic health records (containing cancer types, comorbidities and echo data). Survival data were retrieved from the Statistics Austria Federal Institute. Clinical and pacemaker data of patients with previously diagnosed cancer requiring pacemaker implantation (Group A) were compared to patients with pre-existing pacemaker followed by cancer diagnosis (Group B). Results: Out of 972 included patients, 295 patients (30.3%) had the pacemaker implantation after their first cancer diagnosis (Group A), and 677 patients (69.7%) had already a pacemaker before their first cancer diagnosis (Group B). Cancer types are displayed in Figure 1. The following cancer types were associated with increased likelihood for pacemaker implantation after cancer diagnosis (Group A): kidney cancer (OR 2.07, 95% CI 1.12 to 3.83, P=0.02), lymphomas (OR 2.27, 95% CI 1.21 to 4.26, P=0.01), and eye cancer (OR 9.29, 95% CI 1.03 to 83.50, P=0.047). Patients in Group A were older at pacemaker implantation (76.0 years [IQR 68.0–82.2] vs. 72.1 years [IQR 64.3–78.0], P<0.001), and single-chamber pacemakers were less frequent (21.8% vs. 32.1%, P=0.001). Pacemaker implantation due to bradycardic atrial fibrillation was less frequent in Group A (15.6% vs. 21.8%, P=0.03), but implantation due to an "unspecified" indication was increased (20.6% vs. 12.7%, P=0.002). Patients in Group A had lower pacing threshold at baseline but had a stronger increase in pacing threshold during the follow-up as indicated in Table 1. No differences regarding left or right ventricular function, left or right end-diastolic diameter, or mitral or tricuspid regurgitation were detected between the groups. Patients in Group A had smaller left atria (59.7±10.7mm vs. 63.9±24.0mm, P=0.02) and smaller right atria (57.9±10.4mm vs. 61.2±11.8mm, P=0.001). Patients with cancer diagnosis requiring pacemaker had worse 10-year survival (31.2% vs. 51.1%, log-rank P<0.001) as shown in Figure 1. Conclusion: Kidney cancer, lymphoma, and cancer of the eye were associated with increased probability of pacemaker implantation after cancer diagnosis. The significant increase in pacing threshold in patients undergoing chemotherapy could be associated with chemotherapy-induced cardiotoxicity. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 Future and Emerging Technologies Programme